The Relation of The Available Electronic Learning Efficiencies With The Chemistry High-School Teachers' Performance (Journal of the College of Basic Education, 2022)
This research aims at investigating the relation of the available Electronic learning efficiencies with the chemistry high-school teachers' performance. The researcher has adopted a descriptive design of research to achieve this aim. The population of the research was selected from Baghdad governorate/ Alrusafa discrete by selecting 168 high schools . the sample of the research was chosen randomly in 20% of the whole population consisted of 32 schools . One teacher was assigned from each school so the sample was 32 chemistry high schools teachers. To achieve the aim of this research the researcher has adopted Jiad 2013 scale for Electronic learning efficiencies with forming a chick-list to monitor the teachers' performance inside the classes and accomplishing the psychometric for the tools, next the researcher has applied the two tools on the sample of the study with analyzing the gathered data with the suitable statistic tools. The results has showed the followings:-The degree of availability of electronic skills among female teachers was weak.- Decreased teaching performance among chemistry teachers in the preparatory stage.- There is a strong relationship between the electronic competencies and the teaching performance of female teachers in the preparatory stage for chemistry. In light of the results , the researcher recommended to improve the schools levels in electronic learning by using modern methods of teaching with learning efficiencies and helping students to master them so that they can well done accomplish their expected task. The researcher suggested making similar studies with different variables and different stages.